Cesarea section in adolescents. Hospital Hipólito Unanue. Lima, Perú - Abad, Pedro (2015)
OBJETIVES: To determine the frequency of caesarean sections in pregnant teenagers and maternal and perinatal morbidity. DESIGN: Retrospective study of cases and controls. PLACE AND PERIOD: Hipolito Unanue National Hospital, Lima, Peru, from January 1 to December 31 1999. MATERIAL METHODS: The study of 212 adolescents undergoing cesarean section compared to 966 non-pregnant teens. The information was obtained from the database of Perinatal Information System. RESULTS: adolescents accounted for 19.6% and 13.3% delas models pregnancies abortions; 21.4% of deliveries were vaginal and 17.9% (212) cesareans; 91.2% had no stable union, primigravid 74.1%, 15.7% without prenatal care; 57.3% labor began spontaneously, was cesareada 87.7% first and 85.3% were admitted to operating room as an emergency. The main indications for cesarean section were cephalopelvic disproportion (16.5%) and presentation dystocia (14.6%). The most common postoperative complication was fever (11.8%). There were no maternal or perinatal mortality. CONCLUSIONS: Almost 20% of teenage pregnancies was 17.9% and they ended their pregnancy by cesarean section, cesarean section to be major causes of cephalopelvic disproportion and presentation dystocia.